Formulation of demulsifier for treating Malaysian crude oil emulsion - 304377 Siti Ilyani Rani (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Kimia)) -Universiti Teknologi Malaysia, 2004